Responsabilidad social y su relación con la satisfacción laboral de los colaboradores del multiservicios Sarahi Iquitos 2024 - Olivares Pinedo, Estefany Karina (2025)
The objective of this study was to determine the relationship between social responsibility and job satisfaction among the employees of the Sarahi multiservice in Iquitos 2024, using rigorous procedures and statistical data collection techniques. The design is non-experimental, observing phenomena as they occur and then analyzing them, and it is correlational as it connects concepts, facts, or variables. The most important results show that the reliability coefficient for variable 1 (Social Responsibility) is 0.908, indicating high reliability in the processed data, and the Cronbach's Alpha reliability coefficient for variable 2 (Job Satisfaction) is 0.828. Additionally, Table 03 shows a significant value of zero, indicating that there is a significant link between the variables. The Pearson correlation value is 0.923**. This study highlights the importance of social responsibility as a key factor in improving job satisfaction, providing significant empirical evidence that can be used for future research and organizational policies in the multiservice context.